A study of the females' user perception of women only coach case study of KTM Komuter - Murad, Mirahida; Bachok, Syahriah; Mohamed Osman, Mariana (IIUM Press, 2015)
The study is to assess the female user perception of women only coach of KTM Komuter in Klang Valley area